2017
DOI: 10.1007/s00253-017-8221-9
|View full text |Cite
|
Sign up to set email alerts
|

Deprivation of asparagine triggers cytoprotective autophagy in laryngeal squamous cell carcinoma

Abstract: Laryngeal squamous cell carcinoma (LSCC), one of the most common malignancies in the head and neck, has poor prognosis and high mortality. The need of novel and effective treatment for LSCC is urgent. Asparaginase, an enzyme-depriving asparagine, has been employed for the treatment of various cancers. In this study, we reported for the first time that asparaginase could induce remarkable cytotoxicity and caspase-dependent apoptosis in human LSCC Tu212 and Tu686 cells. Meanwhile, autophagy was triggered by aspa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…NCI-N87 cells were treated with 1.25 µg/mL T-DM1, respectively, for the indicated times, and then stained with Cyto-ID, Hoechst 33342, and/or LysoTracker according to previously described instructions and analyzed with a confocal microscope (Carl Zeiss LSM710, Carl Zeiss, Germany) 50 . Rapamycin (50 nM) was used as the positive control.…”
Section: Confocal Microscopymentioning
confidence: 99%
“…NCI-N87 cells were treated with 1.25 µg/mL T-DM1, respectively, for the indicated times, and then stained with Cyto-ID, Hoechst 33342, and/or LysoTracker according to previously described instructions and analyzed with a confocal microscope (Carl Zeiss LSM710, Carl Zeiss, Germany) 50 . Rapamycin (50 nM) was used as the positive control.…”
Section: Confocal Microscopymentioning
confidence: 99%
“…[ 1 , 5 , 18 , 20 ] Exploration of the autophagy mechanism would open a new positive outlook for laryngeal cancer. [ 17 , 19 , 29 ] However, most researches focused on autophagy only analyzed a signal gene or an autophagic inhibitor. Garcia-Mayea et al performed an immunohistochemistry study to identify the putative relevance of autophagy in laryngeal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Ji et al also indicated the protective role of autophagy in laryngeal cancer cells and provided a new attractive therapeutic strategy for laryngeal cancer with autophagic inhibitors. [ 19 ] Also, Lin et al and Cao et al both proved the protective role of autophagy in laryngeal cancer. [ 18 , 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some studies have demonstrated that anti-tumor drugs could trigger potent autophagy thereby affecting the drug effect [24]. Therefore, many studies have combined anti-tumor drugs with autophagy inhibitors to achieve the desired therapeutic effect [25,26]. In this study, we hypothesized that treatment with PHN alone or combined with an autophagy inhibitor could be a potential therapeutic strategy against LSCC.…”
Section: Introductionmentioning
confidence: 99%